Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2020
DOI: 10.1002/cbic.202000641
|View full text |Cite
|
Sign up to set email alerts
|

Stabilizing AqdC, a Pseudomonas Quinolone Signal‐Cleaving Dioxygenase from Mycobacteria, by FRESCO‐Based Protein Engineering

Abstract: The mycobacterial PQS dioxygenase AqdC, a cofactor‐less protein with an α/β‐hydrolase fold, inactivates the virulence‐associated quorum‐sensing signal molecule 2‐heptyl‐3‐hydroxy‐4(1H)‐quinolone (PQS) produced by the opportunistic pathogen Pseudomonas aeruginosa and is therefore a potential anti‐virulence tool. We have used computational library design to predict stabilizing amino acid replacements in AqdC. While 57 out of 91 tested single substitutions throughout the protein led to stabilization, as judged by… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 74 publications
0
7
0
Order By: Relevance
“…Previous studies indicated that the characteristics of substrate access tunnels can have a decisive influence on enzyme–substrate specificity and activity. In t-PlaF, we focused on T1 and T2 because only these two allow direct access of GPL or LGPL substrates from the membrane in the t-PlaF A configuration. In contrast, to enter into T3, substrates would need to pass through the solvent, which is energetically unfavorable.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies indicated that the characteristics of substrate access tunnels can have a decisive influence on enzyme–substrate specificity and activity. In t-PlaF, we focused on T1 and T2 because only these two allow direct access of GPL or LGPL substrates from the membrane in the t-PlaF A configuration. In contrast, to enter into T3, substrates would need to pass through the solvent, which is energetically unfavorable.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies indicated that the characteristics of substrate access tunnels can have a decisive influence on enzyme-substrate specificity and activity [53][54][55][56]. In t-PlaF, we focused on T1 and T2 because only these two allow direct access of GPL or LGPL substrates from the membrane in the t-PlaF A configuration.…”
Section: Discussionmentioning
confidence: 99%
“…AqdC VIII Mycobacteroides abscessus ATCC 19977 CAM60402.1 pBAD::his8-tev-aqdC-G40K-G220D-Y238W [19] HQD N.f. Nocardia farcinica IFM 10152 BAD60071.1 pET28b::his8-TEV-HQD N.f.…”
Section: Bacterial Strains Hqd Enzymes and Plasmidsmentioning
confidence: 99%
“…A main drawback of using HodC or AqdC for potential application as QQ enzymes is their susceptibility to proteolytic degradation or denaturation in adverse physicochemical conditions, respectively [ 15 , 16 ]. To improve the robustness of mycobacterial AqdC, a recent study used computational library design to predict stabilizing amino acid replacements and to engineer more thermostable variants [ 19 ].…”
Section: Introductionmentioning
confidence: 99%